Prevalence and factors associated with pulmonary arterial hypertension on maintenance hemodialysis patients in Kinshasa, Democratic Republic of Congo: a cross-sectional study - Engole, Yannick Mompango (BMC Nephrol, 2020)
BACKGROUND: Although cardiovascular diseases in particular Pulmonary Arterial Hypertension (PAH) is associated with, high morbid-mortality in chronic hemodialysis, but its magnitude remains paradoxically unknown in sub-Saharan Africa. The aim of this study was to evaluate the prevalence of PAH and associated factors in chronic hemodialysis in Sub-Saharan African population. METHOD: In a cross-sectional study, patients treated with HD for at least 6 months in 4 hemodialysis centers were examined. PAH was defined as estimated systolic pulmonary arterial pressure (sPAP) ≥ 35 mmHg using transthoracic Doppler echocardiography performed 24 h after the HD session. RESULTS: Eighty-five HD patients were included; their average age was 52.6 ± 15.9 years. Fifty-seven patients (67.1%) were male. Mean duration of HD was 13.3 ± 11 months. With reference to vascular access, 12 (14.1%), 29 (34.1%) and 44 (51.8%) patients had AVF, tunneled cuff and temporary catheter, respectively. The underlying cause of ESRD was diabetes in 30 patients (35.3%). The prevalence of PAH was 29.4%. Patients with PAH had more hyponatremia (11 (44%) vs 10 (16.7%), p = 0.010). In multivariate analysis, unsecured healthcare funding (aOR 4, 95% CI [1.18–6.018]), arrhythmia (aOR 3, 95% CI [1.29–7.34]), vascular access change (aOR 4, 95% CI [1.18–7.51]) and diastolic dysfunction (aOR 5, 95% CI [1.35–9.57] were independently associated with PAH. CONCLUSION: One third of hemodialysis patients exhibit PAH, which is independently associated with low socioeconomic status (unsecured funding, vascular access change) and cardiovascular complications (arrhythmia, diastolic dysfunction).